How do general practitioners put preventive care recommendations into practice? A cross-sectional study in Switzerland and France. Issue 10 (6th October 2017) - Sebo, Paul; Cerutti, Bernard; Fournier, Jean-Pascal; Rat, Cédric; Rougerie, Fabien; Senn, Nicolas; Haller, Dagmar M; Maisonneuve, Hubert
Abstract : Objectives: We previously identified that general practitioners (GPs) in French-speaking regions of Europe had a variable uptake of common preventive recommendations. In this study, we describe GPs' reports of how they put different preventive recommendations into practice. Design, setting and participants: Cross-sectional study conducted in 2015 in Switzerland and France. 3400 randomly selected GPs were asked to complete a postal (n=1100) or online (n=2300) questionnaire. GPs who exclusively practiced complementary and alternative medicine were not eligible for the study. 764 GPs (response rate: postal 47%, online 11%) returned the questionnaire (428 in Switzerland and 336 in France). Main outcome measures: We investigated how the GPs performed five preventive practices (screening for dyslipidaemia, colorectal and prostate cancer, identification of hazardous alcohol consumption and brief intervention), examining which age group they selected, the screening frequency, the test they used, whether they favoured shared decision for prostate cancer screening and their definition of hazardous alcohol use. Results: A large variability was observed in the way in which GPs provide these practices. 41% reported screening yearly for cholesterol, starting and stopping at variable ages. 82% did not use any test to identify hazardous drinking. The most common responses for defining hazardous drinking were, for men, ≥21 drinks/week (24%) and ≥4 drinks/occasion for binge drinking (20%), and for women, ≥14 drinks/week (28%) and ≥3 drinks/occasion (21%). Screening for colorectal cancer, mainly with colonoscopy in Switzerland (86%) and stool-based tests in France (93%), was provided every 10 years in Switzerland (65%) and 2 years in France (91%) to patients between 50 years (87%) and 75 years (67%). Prostate cancer screening, usually with shared decision (82%), was provided yearly (62%) to patients between 50 years (74%) and 75–80 years (32%–34%). Conclusions: The large diversity in the way these practices are provided needs to be addressed, as it could be related to some misunderstandingof the current guidelines, to barriers for guideline uptake or, more likely, to the absence of agreement between the various recommendations.